Comparison of behaviour, performance and mortality in restricted and ad libitum-fed growing rabbits. (2nd March 2015) - Dalmau, A.; Abdel-Khalek, A. M.; Ramon, J.; Piles, M.; Sanchez, J. P.; Velarde, A.; Rafel, O.
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of this study was to determine whether rabbits fed in a restricted regimen (75%) showed increased competition for feeding, drinking and use of specific areas of the cages as compared with those provided feed ad libitum. This evaluation was carried out by measuring their space utilisation in the cage, the incidence of agonistic behaviour and rates of mortality. In total, 504 rabbits between 31 and 66 days of age were used in this study. A total of 200 heavy-weight rabbits and 56 light-weight rabbits were randomly housed in 32 cages, each cage containing eight rabbits: 25 cages housing heavy rabbits and seven cages housing the light-weight ones. They were all fed ad libitum (AD). In addition, a total of 208 heavy-weight rabbits and 40 light-weight rabbits were randomly housed in 31 cages, each of them containing eight rabbits: 26 cages housing heavy weight rabbits and five cages housing light-weight ones. They were all fed a restricted diet (R) regimen. The restriction was calculated to be 75% of the feed consumed by the AD group. The total space available in the cage was 3252 cm2, with a stocking density of 24.6 animals/m2. Animals between 32 and 60 days of age from 20 different cages were observed nine times per week (morning or afternoon) by means of scan and focal sampling by one observer. During each period, cages were assessed for 5 min, registering every minute the position of all the animals in relation to Area A (feeder), Area B (central part) or Area C (back and drinker area). The incidence of agonistic behaviour such as displacement, biting and jumping on each other was also assessed. Performance variables such as daily gain and feed conversion ratio, in addition to general health status and mortality rates, were recorded for all rabbits. When the rabbits were under restricted feeding, the competition for feed and drink increased with clear signs of agonistic behaviour such as biting, displacement and animals jumping on top of each other. Although this competition was maintained during the entire growing period, the BW homogeneity between animals in the same cage was similar in both cases, suggesting that all animals could consume similar quantities of feed. The possible advantages of a restricted diet, such as better feed conversion ratio, were observed in this study only in the last few weeks of the growing period.